Clothing preference affects vitamin D status of young women - Büyükuslu, Nihal; Esin, Kübra; Hızlı, Hilal; Sunal, Nihal; Yiğit, Pakize; Garipağaoğlu, Muazzez (Elsevier, 2014)
Vitamin D deficiency is associated with several chronic diseases, which include cardiovascular, autoimmune diseases, and cancer. Several factors such as exposure to sunlight, skin color, dietary habits, and cultural factors affect serum vitamin D levels. We hypothesized that serum vitamin D levels in young women are associated with clothing styles and investigated this via a cross-sectional study that included 100 female students at Istanbul Medipol University. Our study used a questionnaire in order to collect demographic information. Serum calcium, 25-hydroxyvitamin D, alkaline phosphatase, and parathyroid hormone levels were determined via standard laboratory tests. We deployed bioelectrical impedance analysis to measure body composition, and we then determined the body mass index (BMI), waist circumference, and total body fat values. The mean age was 20.9 +/- 2.1 years. Subjects' data were divided into 2 groups based on their clothing styles: covered (Muslim style clothing) and uncovered. Muslim style clothing, which covers the whole body but leaves the face and hands exposed, was worn by 40.0% of the undergraduate students. The mean BMI (in kilograms per meter squared) of the subjects was 23.0 +/- 3.6. The BMI value for the covered students was 24.0 +/- 4.0, and that for the uncovered students was 22.3 +/- 3.1. Of the subjects, 28.0% had a BMI of at least 25 kg/m(2) (overweight). Serum 25-hydroxyvitamin D (in nanograms per milliliter), parathyroid hormone (in picograms per milliliter), alkaline phosphatase (in units per liter), and calcium levels (in milligrams per deciliter) were 21.1 +/- 6.7, 27.5 +/- 9.2, 65.9 +/- 10.9, and 9.0 +/- 0.2 for covered students, respectively, and 29.7 +/- 3.1, 24.3 +/- 6.1, 62.8 +/- 13.2, and 9.0 +/- 0.4, respectively, for uncovered students. The prevalence of vitamin D deficiencies was 55.0% for covered and 20.0% for uncovered students. The vitamin D status was found to be statistically significant and had a negative correlation with the duration of Islamic dressing (P < .05, r = -0.334). We concluded that the vitamin D levels of young women are associated with clothing style, and the age at which a female begins wearing Muslim style clothing is related.
WOS: 000341747100006
PubMed ID: 25156789
Keywords: Vitamin D; Female Students; Clothing Style; BMI; Parathyroid Hormone; Alkaline Phosphatase; Calcium